“Level of Self-Esteem of BSHM Students and Its Effect on Academic Performance.”: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Self-esteem is important for students' academic track as it shows that they have faith inthemselves and are confident in their skills and judgment. It is defined as a positive outlook ononeself and the outside world that inspires courageous actions driven by respect for oneself.According to Cicero, one's ability to trust oneself is essential to success. Vince Lombardi, asports legend, emphasized that confidence is contagious and is the key to success. As BSHMstudents, we address the issue of low self-esteem to assist other students in increasing theirself-esteem.The researchers found out that the school program is highly effective with a 3.56 compositemean; the career program is highly effective with a 3.65 composite mean, and the majorsubject is effective with 3.47 CM, which is only effective in students’ self-esteem. Attendanceis highly effective, with a 3.60 composite mean. Activities are also highly effective, with a 3.58composite mean. The level of self-esteem and academic performance of BSHM studentshave no significant relationship, with self-esteem having an R-value of -0.166 and a t-statvalue of -0.68 with a p-value of.506225.Schools should provide incentives, professors should allow late students, students shouldhave time management skills, and their family should be their source of self-esteem.
Keywords: Hospitality Management